Effectiveness of Honey in Increasing Hemoglobin Levels of Mothers Post Sectio Caesarea - Indah Lestari; Heni Frilasari; Arsy Eka Lestari (Humanistic Network for Science and Technology (HNST), 2019)
The prevalence of surgical delivery assistance (Sectio caesarea) is increasing. During the intrapartal procedure, the mother is at risk of excessive bleeding and has an impact on decreasing hemoglobin levels. The purpose of the study is to prove the effectiveness of honey in increasing the initial hemoglobin levels of mothers Post Sectio Caesarea. The samples of the study were 50 postpartum mothers, who met the criteria of the research. Respondents were taken by random sampling, divided into 24 people in control group and 26 people in experimental group. The dependent variables were HB level and the administration of honey as an independent variable. HB was measured using electric HB and medical record. Data were analyzed by Mann-Whitney test, Wilcoxon Sign Rank test, and Wilcoxon-Mann-Whitney. The results of the showed mean pre-post control and experiment group: 10.36±0.87 vs 10.82±0.35; p value = 0.473; 11.53±0.45 vs 12.87±0.76; p value = 0.028, meaning that the administration of honey was effective in increasing the HB levels of mothers post Sectio caesarea. Honey contains iron (Fe), which is an important micromineral in the body because it can function to form red blood cells. Iron content can synthesize heme formation which increases Hemoglobin levels. Keywords: hemoglobin level; honey; post sectio caesarea